2015
DOI: 10.1166/asl.2015.5944
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure of Shariah-Compliant Companies in Malaysia

Abstract: The study looks at the determinants of capital structure of listed Shariah-compliant companies in Malaysia. It presents a study of the companies included in the Top 100 publicly listed companies in the Main Board of the Bursa Malaysia over the period of 2009 to 2011. The study applies 4 independent variables which are asset tangibility (TANG), growth opportunities (GROWTH), profitability (PROF) and firm size (SIZE while the dependent variable is debt ratio (DR). Panel data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Many scholars have reported that one of the factors that led to this issue was relate with competitive advantage (Lau & Tong, 2008;Ting & Lean, 2012;Zin & Sulaiman, 2011). The failure factors such as weak in strategic planning, lack of capabilities, huge gap in talent and execution skills are the issues or greater challenge that faced by GLCs in achieving competitive advantage (MINDA, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have reported that one of the factors that led to this issue was relate with competitive advantage (Lau & Tong, 2008;Ting & Lean, 2012;Zin & Sulaiman, 2011). The failure factors such as weak in strategic planning, lack of capabilities, huge gap in talent and execution skills are the issues or greater challenge that faced by GLCs in achieving competitive advantage (MINDA, 2009).…”
Section: Introductionmentioning
confidence: 99%